Anterior cruciate ligament injury in elite football: a prospective three-cohort study. - Walden, M.; Hägglund, M.; Magnusson, H.; Ekstrand, J. (Knee surgery, Sports Traumatology. Arthroscopy, 2011)
Anterior cruciate ligament (ACL) injury causes long lay-off time and is often complicated with subsequent new knee injury and osteoarthritis. Female gender is associated with an increased ACL injury risk, but few studies have adjusted for gender-related differences in age although female players are often younger when sustaining their ACL injury. The objective of this three-cohort study was to describe ACL injury characteristics in teams from the Swedish men's and women's first leagues and from several European men's professional first leagues. Over a varying number of seasons from 2001 to 2009, 57 clubs (2,329 players) were followed prospectively and during this period 78 ACL injuries occurred (five partial). Mean age at ACL injury was lower in women compared to men (20.6 ± 2.2 vs. 25.2 ± 4.5 years, P = 0.0002). Using a Cox regression, the female-to-male hazard ratio (HR) was 2.6 (95% CI 1.4-4.6) in all three cohorts studied and 2.6 (95% CI 1.3-5.3) in the Swedish cohorts; adjusted for age, the HR was reduced to 2.4 (95% CI 1.3-4.2) and 2.1 (95% CI 1.0-4.2), respectively. Match play was associated with a higher ACL injury risk with a match-to-training ratio of 20.8 (95% CI 12.4-34.8) and 45 ACL injuries (58%) occurred due to non-contact mechanisms. Hamstrings grafts were used more often in Sweden than in Europe (67 vs. 34%, P = 0.028), and there were no differences in time to return to play after ACL reconstruction between the cohorts or different grafts. In conclusion, this study showed that the ACL injury incidence in female elite footballers was more than doubled compared to their male counterparts, but also that they were significantly younger at ACL injury than males. These findings suggest that future preventive research primarily should address the young female football player.